Potential Sustainability Scenarios for Gringsing Weaving in Bali, Indonesia: How Important is Education? - Pryanka, I Gusti Ayu Agung Virna; Saskara, Ida Ayu Nyoman (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
The Gringsing weaving craft industry in Karangasem, Bali, Indonesia, is a culture-based creative industry with its values ​​and characteristics as a local cultural heritage with innovation and creativity important for developing countries and economic growth. With the rapid modernization of technology, Bali Aga ethnic weavers must adapt to changing times by improving education, skills, and knowledge to maintain the continuity of local traditions. This research aims to determine the probability scenarios for weaving sustainability in Tenganan Pegringsingan Village, Karangasem. This research is quantitative, with primary data from the results of FGDs with experts who will later determine probability scenarios for sustainability. Researchers will place more emphasis on educational probability scenarios to improve the skills and knowledge of artisans. The analysis technique used is SMIC-Prob analysis. The analysis results show that of the five scenarios formulated, there is the best combination with a probability of 0.104, namely the scenario of artisans producing as usual, opening a fashion stall, increasing production, and increasing knowledge. The conclusion of the sensitivity of the scenario shows the highest elasticity in the sustainability of Gringsing weaving by realizing an educational scenario to increase skills and knowledge of 1.102. It can be concluded that the sustainability of weaving is determined mainly by the educational scenario to improve the skills and knowledge of artisans. Training programs and instilling character values ​​as support for weaving artisans need to be improved to maintain the sustainability and development of the weaving.